2012
DOI: 10.1371/journal.pone.0045938
|View full text |Cite
|
Sign up to set email alerts
|

Altered Brain Activity during Reward Anticipation in Pathological Gambling and Obsessive-Compulsive Disorder

Abstract: BackgroundPathological gambling (PG) and obsessive-compulsive disorder (OCD) are conceptualized as a behavioral addiction, with a dependency on repetitive gambling behavior and rewarding effects following compulsive behavior, respectively. However, no neuroimaging studies to date have examined reward circuitry during the anticipation phase of reward in PG compared with in OCD while considering repetitive gambling and compulsion as addictive behaviors.Methods/Principal FindingsTo elucidate the neural activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
71
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(83 citation statements)
references
References 41 publications
5
71
1
Order By: Relevance
“…As has been shown in SUD [34,36], activation in the ventral striatum during gain anticipation correlated negatively with impulsivity measures. In line with that, Choi et al [40] reported reduced activation of the ventromedial caudate nucleus both during anticipation of gain and loss in patients with GD. On the other hand, Miedl et al [27] reported an enhanced activity of ventral striatal and posterior cingulate during reward processing as derived from contrasting winning versus losing situations.…”
Section: Neglect Of Other Areas In Lifesupporting
confidence: 77%
“…As has been shown in SUD [34,36], activation in the ventral striatum during gain anticipation correlated negatively with impulsivity measures. In line with that, Choi et al [40] reported reduced activation of the ventromedial caudate nucleus both during anticipation of gain and loss in patients with GD. On the other hand, Miedl et al [27] reported an enhanced activity of ventral striatal and posterior cingulate during reward processing as derived from contrasting winning versus losing situations.…”
Section: Neglect Of Other Areas In Lifesupporting
confidence: 77%
“…In healthy participants, insula responsivity to near-miss outcomes correlated positively with their trait susceptibility to gambling distortions on a self-report scale (6,38). With a monetary incentive delay task in treatment-seeking pathological gamblers, overactivity of anterior insula during loss anticipation was correlated with gambling severity scores (39). These effects may be mediated by the established role of the insula in the representation of bodily states, i.e., interoception (40).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found diminished, normal or even increased BOLD responses in disordered gamblers using a variety of fMRI tasks. For example, disordered gamblers showed attenuated ventral striatal responses during reward anticipation as well as in response to monetary wins (Balodis et al 2012;Choi et al 2012). A recent study found no abnormal processing in reward anticipation but higher ventral striatum activity during loss anticipation (Romanczuk-Seiferth et al 2014).…”
Section: Neurobiology Of Disordered Gamblingmentioning
confidence: 99%